Vibro-Acoustics for Reli-ability Modeling of Un-derwater Pipeline using Wireless Sensor Network (WSN), with Minimum Energy Consumption - Saleh, Yusuf; Sani Yahya, Muhammad; Bukar Dala, Aliyu (International Journal of Engineering and Technology, 2018)
WSN is a network of clusters of sensors nodes which sense the parameter and communicates to a server. Target is to develop underwater pipeline monitoring system remotely with lower energy consumption. Reliability maintenance will effectively give optimum performance of pipeline system operation.Â Reliability ensures optimum performance in the range of operation based on the behavior of the system. Validation of the mathematical model for the flow in pipeline system is used to study vibrations as elements that affect the reliability of the pipeline. In this, the focus is to validate and model the reliability for the pipeline system from the vibrations for predictive maintenance and optimum performance. Subsequently, vibro-acoustics will be used to model the reliability equation. A software can be developed for simulating the reliability model for pipeline system behavior from the vibration factors and use for predictive maintenance. Reliability factors of mean time to failure, repair and others will be put in to use to develop the original model for the pipeline. A hypothesis of 90% predictive model from the reliability under pipeline system behavior will be developed.Â Â